Left hemicolectomy and low anterior resection in colorectal cancer patients: Knight–griffen vs. transanal purse-string suture anastomosis with no-coil placement - Ammendola, Michele; Filice, Francesco; Battaglia, Caterina; Romano, Roberto; Manti, Francesco; Minici, Roberto; de'Angelis, Nicola; Memeo, Riccardo; Laganà, Domenico; Navarra, Giuseppe; Montemurro, Severino; Currò, Giuseppe (Frontiers in Surgery, 2023)
Background Colorectal cancer (CRC) is considered one of the most frequent neoplasms of the digestive tract with a high mortality rate. Left hemicolectomy (LC) and low anterior resection (LAR) with minimally invasive laparoscopic and robotic approaches or with the open technique are the gold standard curative treatment. Materials and methods Seventy-seven patients diagnosed with CRC were recruited between September 2017 and September 2021. All patients underwent a preoperative staging with a full-body CT scan. The goal of this study was to compare both types of surgeries, LC-LAR LS with Knight–Griffen colorectal anastomosis and LC-LAR open with Trans-Anal Purse-String Suture Anastomosis (the TAPSSA group), by positioning a No-Coil transanal tube (SapiMed Spa, Alessandria, Italy), in terms of postoperative complications such as prolonged postoperative ileus (PPOI), anastomotic leak (AL), postoperative ileus (POI), and hospital stay. Results The patients were divided into two groups: the first with 39 patients who underwent LC and LAR in LS with Knight–Griffen anastomosis (Knight–Griffen group) and the second with 38 patients who underwent LC and LAR by the open technique with the TAPSSA group. Only one patient who underwent the open technique suffered AL. POI was 3.76 ± 1.7 days in the TAPSSA group and 3.07 ± 1.3 days in the Knight–Griffen group. There were no statistically significant differences in terms of AL and POI between the two different groups. Conclusion The important point that preliminarily emerged from this retrospective study was that the two different techniques showed similarities in terms of AL and POI, and therefore, all the advantages reported in the previous studies pertaining to No-Coil also hold good in this study regardless of the surgical technique used. However, randomized controlled trials are needed to confirm these findings.